The Bond Strength of the Bonded Bracket to Enamel Surface Treated with Acid and Microetcher - Hussain A Obaidi; Muzahim H Hanna (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate shear and tensile bond strengths of the bonded brackets to the enamel surfaces treated with acid and microetcher. Materials and methods: The sample include 30 intact extracted upper left first premolars, the teeth were collected from orthodontics clinic and private clinics. The sample was grouped into three groups (10 teeth for each group), which were: acid etched, microetched at 5mm distance, and microetched at 10mm distance.. Stainless steel brackets (Roth System) were bonded to the buccal enamel surfaces utilizing light cure composite (transbondTM XT) according to the manufacturer instructions. All the groups were thermocycled, the temperature range is 5 + 3 ºC to 50 + 3 ºC with a 30 seconds dwell time in each bath. The shear and tensile bond strengths of the bonded bracket were measured by using the shear and tensile Universal testing machine. The results were analyzed statistically; that include: Descriptive, ANOVA and Duncan's testes at p≤ 0.05 significant level. Results: It was reveled that the shear and tensile bond strength values of the bonded brackets to enamel treated with the acid were greater significantly than that treated with microetcher. Conclusions: The acid agent is considered the most practical conditioner to the enamel to achieve strong shear and tensile bond strengths.